Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c8py00707a
|View full text |Cite
|
Sign up to set email alerts
|

A facile route to bespoke macro- and mesoporous block copolymer microparticles

Abstract: A facile and versatile strategy to fabricate macro- and mesoporous block copolymer microparticles with bespoke characteristics using supercritical CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…33 Previously, we reported RAFT controlled dispersion polymerisation in scCO 2 as a unique and facile route to create multigram quantities of nanostructured microparticulate BCPs. 14,34,35 Moreover, we have also demonstrated that the sizes of the microparticles can be controlled reproducibly from 300 nm through to 5 μm. 36 Very recently, we developed a facile and versatile approach to convert these nanostructured microparticles into porous microparticles via swelling/deswelling.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…33 Previously, we reported RAFT controlled dispersion polymerisation in scCO 2 as a unique and facile route to create multigram quantities of nanostructured microparticulate BCPs. 14,34,35 Moreover, we have also demonstrated that the sizes of the microparticles can be controlled reproducibly from 300 nm through to 5 μm. 36 Very recently, we developed a facile and versatile approach to convert these nanostructured microparticles into porous microparticles via swelling/deswelling.…”
Section: Introductionmentioning
confidence: 65%
“…The swelling process of the PMMA-b-P4VP BCP microparticles in ethanol followed our earlier published procedures. 34 The original BCP microparticles (50 mg) were fully dispersed in alcohol (3 ml) in a glass vial (3.5 ml) and shaken 3 times by hand over a two-hour period. The particles were then left standing until they settled to the bottom of the vial.…”
Section: Porosity Control By Degree Of Crosslinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…12 -200 nm have already been achieved in BPC microparticles of PMMA-b-P4VP by altering the molecular weight of the two blocks. 31 Furthermore, the templated synthesis of other BCP morphologies (e.g. lamellar, etc.)…”
mentioning
confidence: 99%